Preliminary studies on synthesis and surface-functionalization of perylene diimide-doped silica nanoparticles prepared via reverse microemulsion - VALERIE CHRISTIE, MICLAT (Archīum Ateneo, 2014)
Recent developments in the field of therapeutic devices and bioimaging showed that silica nanoparticles hold a lot of potential as theranostic device due to its biocompatibility, stability, and chemical versatility. SNPs' porosity and tunable sizes make t